Catalyst and method for producing compound by gas phase oxidation reaction using the same
Patent Information
- Application Number
- CN202610927057.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2021-03-03
- Filing Date
- 2022-02-24
- Publication Date
- 2026-10-27
AI Technical Summary
但是,专利文献4中不仅催化剂的制造方法变得复杂,而且作为实用催化剂所要求的催化剂性能不足,处于期待进一步提高催化剂性能、阐明可能成为其原因的物性数据的状况
[0041]本发明的催化剂在气相催化氧化反应或气相催化氧化脱氢反应中保持高选择率并且对提高收率非常有效。特别是在以丙烯、异丁烯、叔丁醇等作为原料制造相应的不饱和醛、不饱和羧酸的情况下是有用的。
Smart Images

Figure CN122974332A_ABST
Abstract
Description
[0001] This application is a divisional application of Chinese patent application No. 202280018533.5, filed on February 24, 2022. Technical Field
[0002] This invention relates to catalysts and gas-phase oxidation reactions using the catalysts, particularly methods for producing unsaturated aldehydes and / or unsaturated carboxylic acids or conjugated dienes. Background Technology
[0003] In industry, methods for producing corresponding unsaturated aldehydes and unsaturated carboxylic acids using propylene, isobutylene, tert-butanol, etc., as raw materials, and gas-phase catalytic oxidation methods for producing 1,3-butadiene from butenes are widely implemented. In particular, many methods for producing corresponding acrolein and acrylic acid using propylene as raw material have been reported as a means to improve their yield (e.g., patent documents 1, 2, etc.).
[0004] Patent Document 3 describes a method for preparing composite metal oxide catalysts with two or more different compositions and filling multiple layers in a manner that stacks two or more layers along the tube axis. By filling the catalyst in a manner where the content of bismuth relative to molybdenum decreases from the gas inlet side to the gas outlet side and the content of iron relative to molybdenum increases from the gas inlet side to the gas outlet side, the reaction bath temperature is kept low even under high load conditions. Thus, no prior art has been found that, in the process of producing the corresponding unsaturated aldehydes and / or unsaturated carboxylic acids from olefins, improving the total yield of unsaturated aldehydes and / or unsaturated carboxylic acids (hereinafter referred to as "effective yield") itself, and while keeping the reaction bath temperature low even under high load conditions, maintains an improved effective yield and stable production.
[0005] Furthermore, Patent Document 4 proposes a method for controlling the peak ratio determined by Raman spectroscopy within a specific numerical range. However, Patent Document 4 not only complicates the catalyst manufacturing method but also fails to meet the required catalyst performance for practical use, leaving the situation open to further improvements in catalyst performance and the clarification of physical property data that may be the cause.
[0006] Existing technical documents
[0007] Patent documents
[0008] Patent Document 1: International Publication No. 2016 / 136882
[0009] Patent Document 2: Japanese Patent Application Publication No. 2017-024009
[0010] Patent Document 3: International Publication No. 2015 / 008815
[0011] Patent Document 4: Japanese Patent Application Publication No. 2020-142221 Summary of the Invention
[0012] The problem that the invention aims to solve
[0013] Although improvements have been sought through the methods described above, further yield improvements are required when using the partial oxidation reactions of olefins such as propylene and isobutylene, and tert-butanol to produce the corresponding unsaturated aldehydes and / or unsaturated carboxylic acids. For example, the yield of the target product affects the amount of olefins such as propylene and isobutylene, and tert-butanol required for production, significantly impacting manufacturing costs. Furthermore, the continuous operation at low yields generates a large amount of byproducts, placing a heavy burden on the purification process and potentially increasing the time and operating costs of purification. In addition, depending on the type of byproduct, these byproducts sometimes accumulate on the catalyst surface and in the gas flow channels near the catalyst. Since these byproducts cover the necessary reactive sites on the catalyst surface, reducing catalyst activity, it is necessary to forcibly increase the activity, necessitating an increase in the reaction bath temperature. This results in thermal stress on the catalyst, leading to a reduction in lifetime, a further decrease in selectivity, and ultimately, a decrease in yield. Furthermore, it is considered that the pressure increase within the system due to byproduct accumulation can reduce selectivity and yield; and depending on the situation, a sudden increase in internal pressure can sometimes cause abnormal temperatures and reaction runaway. Imagine an extended shutdown under these conditions, requiring system cleaning and catalyst replacement.
[0014] means for solving problems
[0015] Therefore, the purpose of this invention is to provide a catalyst capable of producing unsaturated aldehydes, unsaturated carboxylic acids, or conjugated dienes with high selectivity and high yield.
[0016] That is, the present invention relates to the following 1) to 8). 1)
[0018] A catalyst comprising molybdenum, bismuth and iron, wherein the catalyst has an R1 of more than 0.45 and less than 5.00 as represented by the following formula (1).
[0019] R1 = (886 cm⁻¹) determined by Raman spectroscopy -1 ±5cm -1 (maximum value of the peak at 354cm) ÷ (354cm) -1 ±5cm -1 (the maximum value of the peak at the location)……(1). 2)
[0021] A catalyst comprising molybdenum, bismuth, and iron, wherein the catalyst has an R² value of 951.4 cm⁻¹ as expressed by formula (2). -1 And above 959.0cm -1 the following.
[0022] R2 = produces 952 cm⁻¹ as determined by Raman spectroscopy. -1 ±7cm -1 wavenumber of the peak at the maximum value / cm -1 ……(2). 3)
[0024] A catalyst comprising molybdenum, bismuth and iron, wherein the catalyst has an R3 of 0.21 or more as represented by the following formula (3).
[0025] R1 = (886 cm⁻¹) determined by Raman spectroscopy -1 ±5cm -1 (maximum value of the peak at 354cm) ÷ (354cm) -1 ±5cm -1 (the maximum value of the peak at that point)……(1)
[0026] R2 = produces 952 cm⁻¹ as determined by Raman spectroscopy. -1 ±7cm -1 wavenumber of the peak at the maximum value / cm -1 ……(2)
[0027] R3=2.95×R1+0.33×R2-315……(3). 4)
[0029] The catalyst as described in any one of 1) to 3) above, wherein the composition of the active component of the catalyst is represented by the following formula (I).
[0030] Mo a1 Bi b1 Ni c1 Co d1 Fe e1 X f1 Y g1 Z h1 O i1 ……(I)
[0031] In formula (I), Mo, Bi, Ni, Co, and Fe represent molybdenum, bismuth, nickel, cobalt, and iron, respectively; X refers to at least one element selected from tungsten, antimony, tin, zinc, chromium, manganese, magnesium, silicon, aluminum, cerium, and titanium; Y refers to at least one element selected from sodium, potassium, cesium, rubidium, and thallium; and Z refers to elements belonging to groups 1 to 16 of the periodic table and selected from elements other than Mo, Bi, Ni, Co, Fe, X, and Y. One element is missing. a1, b1, c1, d1, e1, f1, g1, h1, and i1 represent the number of atoms of molybdenum, bismuth, nickel, cobalt, iron, X, Y, Z, and oxygen, respectively. When a1=12, 0<b1≤7, 0≤c1≤10, 0<d1≤10, 0<c1+d1≤20, 0≤e1≤5, 0≤f1≤2, 0≤g1≤3, 0≤h1≤5, and i1 = a value determined by the oxidation state of each element. 5)
[0033] The catalyst as described in any one of 1) to 4) above, wherein the catalyst is a catalyst on an inert support on which the active catalytic component is supported. 6)
[0035] The catalyst as described in 5) above, wherein the inert support is silicon dioxide, alumina, or a combination of silicon dioxide and alumina. 7)
[0037] The method for manufacturing the catalyst according to any one of 1) to 6) above, wherein the manufacturing method includes a preparation step of preparing a preparation solution by adding each of the supply source compounds containing molybdenum, bismuth and iron to a solvent or solution and integrating and heating, wherein the pH of the preparation solution is adjusted to the range of 1.0 to 7.5 before the iron raw material is added. 8)
[0039] A method for producing unsaturated aldehydes and / or unsaturated carboxylic acids, wherein the method uses any one of the catalysts described in 1) to 6) above.
[0040] Invention Effects
[0041] The catalyst of this invention maintains high selectivity in gas-phase catalytic oxidation or gas-phase catalytic dehydrogenation reactions and is highly effective in improving yields. It is particularly useful in the production of corresponding unsaturated aldehydes and unsaturated carboxylic acids from raw materials such as propylene, isobutylene, and tert-butanol. Attached Figure Description
[0042] Figure 1 The figure shows the Raman spectroscopy results of catalyst 1 in Example 1.
[0043] Figure 2 To illustrate the effect of Gaussian function on Figure 1 A graph illustrating an example of the results obtained through peak separation. In the graph, the points represent the actual data, the filled regions represent the individual fitted Gaussian functions, and the solid lines represent the fitted curves obtained by summing them. Detailed Implementation
[0044] The present invention will now be described in detail. It should be noted that, in this specification, the above-described gas-phase catalytic oxidation reaction and gas-phase catalytic dehydrogenation reaction are sometimes collectively referred to as oxidation reactions.
[0045] [About R1]
[0046] The catalyst of the present invention is characterized in that R1, represented by the above formula (1), is 0.45 or more and 5.00 or less.
[0047] R1 is the 886 cm⁻¹ measured by Raman spectroscopy. -1 ±5cm -1 The maximum value of the peak at that point divided by 354 cm -1 ±5cm -1 The value obtained by taking the maximum value of the peak at that point is essentially 886 cm⁻¹. -1 ±5cm -1 The peak at this location is the maximum value. This peak is unassigned in the literature, and its details are unclear, but the inventors believe it is related to the amount of O-Mo bonds in molybdate (MoO4). The inventors found that when R1 is high, it exhibits low activity and high selectivity, and when R1 is low, it exhibits high activity and low selectivity; therefore, there is an optimal range of values for R1.
[0048] That is, the catalyst of the present invention is based on the discovery that high selectivity and high yield can be achieved by having an R1 of 0.45 or more and 5.00 or less.
[0049] The lower limit of R1 is more preferably 0.46, and even more preferably 0.47, 0.48, 0.49, 0.50, 0.51, and 0.52. The upper limit of R1 is more preferably 4.50, and even more preferably 4.25, 4.00, 3.75, 3.50, 3.25, 3.00, 2.75, 2.50, 2.25, 2.00, 1.75, 1.50, 1.25, 1.00, 0.75, 0.70, 0.65, 0.60, and 0.55. In other words, the preferred range for the value of R1 is set by the above-mentioned upper and lower limits, for example, 0.51 or higher and 3.00 or lower, and most preferably 0.52 or higher and 0.55 or lower.
[0050] It should be noted that the Raman spectroscopy determination can be performed using known methods, such as the following equipment. A WP 785 Raman Spectrometer manufactured by Wasatch Photonics was used as the Raman spectrometer, an I0785MM0350MF manufactured by Innovative Photonic Solutions was used as the laser module, a WP785-RP manufactured by Wasatch Photonics was used as the non-contact probe, and Panorama Wasatch 4.0 manufactured by Wasatch Photonics was used as the software for analysis. Raman spectroscopy determination was performed under the following conditions: excitation laser wavelength 785 nm, laser power 240 mW–480 mW, laser irradiation time 50 ms, and cumulative number of irradiations 64. The catalyst used for the determination was not specially treated and was directly contacted with the probe for measurement. However, if the ambient noise was high, the determination was performed in a dark room. The measured data were background corrected using the aforementioned software, fitted using a Gaussian function (Equation (4)), and peak separation was performed.
[0051] y=(i'- )×exp{-(x-(p- )) 2 ÷(w- ) 2}……(4)
[0052] Where y: Gaussian function (wavenumber x / cm) -1 (function)
[0053] p- : Generate the first Peak position of the maximum value of each peak / cm -1
[0054] w- : No. Peak width per cm -1
[0055] i'- :(No. (the maximum value of each peak)
[0056] exp: an exponential function with base e.
[0057] In the above, with The corresponding peaks are assigned as follows.
[0058] 0:354cm -1 ±5cm -1 peak
[0059] 1: 782cm -1 ±5cm -1 peak
[0060] 2: 820cm -1 ±5cm -1 peak
[0061] 3: 868cm -1 ±5cm -1 peak
[0062] 4: 886cm -1 ±5cm -1 peak
[0063] 5: 900cm -1 ±5cm -1 peak
[0064] 6: 940cm -1 ±4cm -1 peak
[0065] 7: 952cm -1 ±7cm -1 peak
[0066] 8: 968cm -1 ±5cm -1 peak
[0067] 9:989cm -1 ±5cm -1 peak
[0068] [About R2]
[0069] The catalyst of the present invention is characterized in that R2, as expressed by the above formula (2), is 951.4 cm. -1 Above and 959.0cm -1 the following.
[0070] R2 represents the 952 cm⁻¹ value obtained by Raman spectroscopy. -1 ±7cm -1 The wavenumber of the peak maxima is obtained by fitting the measured data according to equation (4) above, parameter p-7. The inventors believe that R2 represents the distance or intensity of the bond associated with oxygen atoms in nickel molybdate or cobalt molybdate as determined by Raman spectroscopy. The inventors found that when R2 increases, the oxygen (bulk lattice oxygen used in the oxidation reaction) in nickel molybdate or cobalt molybdate is strongly bound, thus exhibiting low activity and high selectivity. Conversely, when R2 decreases, the oxygen binding is relaxed, exhibiting high activity and low selectivity. Therefore, there is an optimal range of values for R2.
[0071] That is, it was found that the catalyst of the present invention has an R2 of 951.4 cm. -1 Above and 959.0cm -1 The following methods can achieve high selectivity and high yield.
[0072] As the lower limit of R2, a more preferred value is 951.5cm. -1 Further optimization yielded a value of 951.7cm. -1 951.9cm -1 952.1cm -1 952.2cm -1 Furthermore, as an upper limit for R2, 958.0 cm is more preferable. -1 Further optimization yielded a value of 957.0 cm. -1 956.0cm -1 955.0cm -1 954.0cm -1 953.0cm -1 952.8cm -1 952.6cm -1 That is, the preferred range for the value of R2 is set according to the aforementioned upper and lower limits, for example, 951.5 cm. -1 Above and 954.0cm -1 The optimal value is 952.2cm. -1 Above and 952.6cm -1 the following.
[0073] [About R3]
[0074] The catalyst of the present invention has an R3 of 0.21 or higher, as expressed by the above formula (3). The essence of R3 is the result of an increased selectivity observed under conditions where a certain relationship is observed between R1 and R2. R3 is a parameter obtained by regression of the values of R1, R2, and selectivity. That is, it is considered that if the amount of O-Mo bonds in (R1) is high and / or the bond strength related to oxygen atoms in nickel molybdate or cobalt molybdate is strong, then R3 exhibits a high value. The inventors discovered a relationship between this numerical range and the effective yield.
[0075] As a lower limit for R3, 0.30 is more preferred, and 0.36, 0.40, 0.50, 0.65, 0.70, and 0.80 are even more preferred. Furthermore, there is no particular limitation on the upper limit of R3, which can be approximately 2.0, and is even more preferred to be approximately 1.0.
[0076] [Regarding catalyst composition]
[0077] The catalyst active component contained in the catalyst of the present invention preferably has a composition represented by the following formula (I).
[0078] Mo a1 Bi b1 Ni c1 Co d1 Fe e1 X f1 Y g1 Z h1 O i1 ……(I)
[0079] In formula (I), Mo, Bi, Ni, Co, and Fe represent molybdenum, bismuth, nickel, cobalt, and iron, respectively; X refers to at least one element selected from tungsten, antimony, tin, zinc, chromium, manganese, magnesium, silicon, aluminum, cerium, and titanium; Y refers to at least one element selected from sodium, potassium, cesium, rubidium, and thallium; and Z refers to at least one element belonging to groups 1 to 16 of the periodic table and selected from elements other than Mo, Bi, Ni, Co, Fe, X, and Y. Let a1, b1, c1, d1, e1, f1, g1, h1, and i1 represent the number of atoms of molybdenum, bismuth, nickel, cobalt, iron, X, Y, Z, and oxygen, respectively. When a1 = 12, the following conditions apply: 0 < b1 ≤ 7, 0 ≤ c1 ≤ 10, 0 < d1 ≤ 10, 0 < c1 + d1 ≤ 20, 0 ≤ e1 ≤ 5, 0 ≤ f1 ≤ 2, 0 ≤ g1 ≤ 3, 0 ≤ h1 ≤ 5, and i1 = a value determined by the oxidation state of each element.
[0080] In the above formula (I), when a1=12, the preferred range of b1~i1 is as follows.
[0081] The preferred lower limit of b1 is 0.2, 0.5, 0.6, and 0.7, with the most preferred value being 0.8. The preferred upper limit of b1 is 5, 3, 2, 1.6, 1.4, and 1.2, with the most preferred value being 1.1. That is, the optimal range of b1 is 0.8 ≤ b1 ≤ 1.1.
[0082] The preferred lower limit of c1 is 1, 1.5, 2.0, 2.2, and 2.4, with the most preferred value being 2.5. The preferred upper limit of c1 is 5, 4, 3.8, 3.6, and 3.4, with the most preferred value being 3.2. That is, the optimal range of c1 is 2.5 ≤ c1 ≤ 3.2.
[0083] The preferred lower limit of d1 is 3, 4, 5, 5.3, 5.5, 5.7, with the most preferred value being 5.8. The preferred upper limit of d1 is 8, 7, 6.5, 6.3, 6.1, with the most preferred value being 6.0. That is, the optimal range of d1 is 5.8 ≤ d1 ≤ 6.0.
[0084] The preferred lower limit of e1 is 0.5, 1, 1.2, 1.4, with the most preferred value being 1.5. The preferred upper limit of e1 is 4, 3, 2.5, 2.3, 2.1, with the most preferred value being 2.0. That is, the optimal range of e1 is 1.5 ≤ e1 ≤ 2.0.
[0085] The upper limit of f1 is preferably 8, 7, 6, and 5 respectively. That is, the optimal range of f1 is 0 ≤ f1 ≤ 5.
[0086] The preferred lower limit of g1 is 0, 0.02, 0.04, 0.05, and 0.06, with the most preferred value being 0.07. The preferred upper limit of g1 is 1.5, 1, 0.5, 0.2, and 0.15, with the most preferred value being 0.10. That is, the optimal range of g1 is 0.07 ≤ g1 ≤ 0.10.
[0087] The upper limit of h1 is preferably 8, 7, 6, and 5 respectively. That is, the optimal range of h1 is 0 ≤ h1 ≤ 5.
[0088] It should be noted that the case with two or fewer Y values is preferred, and the case with only one Y value is particularly preferred. Additionally, the case where f1 and h1 are both 0 is particularly preferred.
[0089] [Regarding load]
[0090] The catalyst obtained by loading the pre-calcined powder obtained by pre-calcining the catalyst active component onto an inert support is particularly effective as the catalyst of the present invention.
[0091] As the material for the inert support, known substances such as alumina, silicon dioxide, titanium dioxide, zirconium oxide, niobium oxide, silicon dioxide-alumina, silicon carbide, carbides, block talc, and mixtures thereof can be used. Furthermore, there are no particular restrictions on the particle size, water absorption rate, mechanical strength, crystallinity of each crystalline phase, or mixing ratio of the inert support; the appropriate range should be selected considering the performance, formability, and production efficiency of the final catalyst. The mixing ratio of the support to the pre-calcined powder is calculated as the loading rate based on the feed mass of each raw material using the following formula.
[0092] Loading rate (mass%) = (mass of pre-calcined powder used in molding) / {(mass of pre-calcined powder used in molding) + (mass of carrier used in molding)} × 100
[0093] The preferred upper limit of the above-mentioned load rate is 80% mass, and more preferably 60% mass.
[0094] Furthermore, the preferred lower limit of the above-mentioned load rate is 20% by mass, and more preferably 30% by mass. That is, the most preferred range of the load rate is 30% by mass or more and 60% by mass or less.
[0095] It should be noted that, as an inert carrier, silica and / or alumina are preferred, and a mixture of silica and alumina is particularly preferred.
[0096] It should be noted that a binder is preferably used during loading. Specific examples of usable binders include: water, ethanol, methanol, propanol, polyols, polyvinyl alcohol as a polymer binder, and silica sol aqueous solutions as inorganic binders. Ethanol, methanol, propanol, and polyols are preferred, as are diols such as ethylene glycol and triols such as glycerol. An aqueous solution with a glycerol concentration of 5% by mass or more is particularly preferred. By using an appropriate amount of glycerol aqueous solution, the formability becomes good, and a catalyst with high mechanical strength and high performance can be obtained. The amount of these binders used is typically 2 to 60 parts by mass relative to 100 parts by mass of pre-calcined powder, and preferably 10 to 30 parts by mass in the case of an aqueous glycerol solution. During loading, the binder and pre-calcined powder can be supplied to the molding machine alternately or simultaneously.
[0097] [Method for manufacturing the catalyst of the present invention]
[0098] The method for manufacturing the catalyst of the present invention comprises the following steps: (a) dispersing a compound containing each of the above-mentioned metals or a compound containing multiple of the above-mentioned metals in water to prepare an aqueous solution or aqueous dispersion of these compounds (hereinafter, both will be referred to as slurry); (b) drying the slurry obtained in step (a) to obtain a dried slurry body; (c) molding the dried slurry body obtained in step (b); and (d) calcining the coated molded article obtained in step (c), but is not limited thereto.
[0099] <(a) Process>
[0100] In process (a), there are no particular restrictions on the starting materials for each element. For example, as a raw material for molybdenum, molybdenum oxides such as molybdenum trioxide, molybdic acid, ammonium paramolybdate, ammonium metamolybdate, or their salts, can be used; molybdenum-containing heteropoly acids such as phosphomolybdic acid and silicomolybdic acid or their salts can be used.
[0101] As raw materials for bismuth components, bismuth salts such as bismuth nitrate, bismuth carbonate, bismuth sulfate, and bismuth acetate, as well as bismuth trioxide and metallic bismuth, can be used. These raw materials can be used directly in solid form or in the form of aqueous solutions or nitric acid solutions, or slurries of bismuth compounds generated from their aqueous solutions. It is preferred to use nitrates or their solutions, or slurries generated from their solutions.
[0102] As starting materials for other constituent elements, ammonium salts, nitrates, nitrites, carbonates, hypocarbonates, acetates, chlorides, inorganic acids, salts of inorganic acids, heteropoly acids, salts of heteropoly acids, sulfates, hydroxides, organic acid salts, oxides, or mixtures thereof of metal elements commonly used in such catalysts can be used in combination, with ammonium salts and nitrates being preferred.
[0103] These compounds containing active ingredients can be used alone or in combination of two or more. A slurry can be obtained by uniformly mixing various compounds containing active ingredients with water. There is no particular limitation on the amount of water used in the slurry, as long as it is sufficient to completely dissolve all the compounds used or to achieve uniform mixing. The amount of water used should be appropriately determined considering the drying method and conditions. Generally, the amount of water used is between 100 and 2000 parts by mass relative to the total mass of 100 parts by mass of the compounds used in slurry preparation. While a larger amount of water can be used, excessive water increases the energy cost of the drying process and may lead to incomplete drying, resulting in several disadvantages.
[0104] The slurry of the supply source compounds for the aforementioned constituent elements is preferably prepared by the following methods: (a) a method of mixing the aforementioned supply source compounds in one step; (b) a method of mixing the aforementioned supply source compounds in one step followed by aging treatment; (c) a method of mixing the aforementioned supply source compounds in steps; (d) a method of repeatedly performing the method of mixing and aging the aforementioned supply source compounds in steps; and a method of combining (a) to (d). Here, aging refers to "processing industrial raw materials or semi-finished products under specific conditions such as a certain time and a certain temperature to achieve the desired physical or chemical properties, or to carry out a specified reaction, etc." It should be noted that in this invention, the aforementioned "certain time" refers to a range of 5 minutes or more and 24 hours or less, and the aforementioned "certain temperature" refers to a range above room temperature and below the boiling point of the aqueous solution or aqueous dispersion. From the perspective of the activity and yield of the final catalyst, method (c) of mixing the above-mentioned source compounds in steps is preferred; method of preparing a solution in which each raw material is completely dissolved and mixed with the mother liquor in steps is even more preferred; and method of mixing various mixtures of alkali metal solutions and nitrates in the mother liquor from which the molybdenum raw material is prepared into a blending solution or slurry is most preferred. However, it is not necessary to mix all the catalyst constituent elements in this step; some elements or amounts may be added in subsequent steps.
[0105] In this invention, the shape of the stirring blades of the agitator used to mix the necessary active ingredients is not particularly limited. Any stirring blade, such as a single-stage propeller blade, turbine blade, paddle blade, inclined paddle blade, spiral blade, anchor blade, belt blade, or large grid blade, can be used; or two or more stages of the same type of blade or different types of blades can be used in the vertical direction. In addition, baffles (deflectors) can be installed in the reaction tank as needed.
[0106] [Regarding pH adjustment]
[0107] To achieve the catalyst of the present invention, a particularly preferred manufacturing method is as follows: In step (a), in the preparation step of preparing a preparation solution by adding each source compound containing molybdenum, bismuth, and iron to a solvent or solution and integrating and heating, the pH of the preparation solution is adjusted to a range of 1.0 to 7.5 before the iron raw material is added. As detailed below, the method for adjusting the pH can be by lowering the pH by adding nitric acid or the like, or by raising the pH by adding ammonia or the like.
[0108] The lower limit of pH is more preferably 1.5, and further preferably 1.8, 2.0, 2.2, 2.5, 2.7, 3.0, 3.1, 3.2, 3.5, 3.7, 3.8, and 3.9. The upper limit of pH is more preferably 7.3, and further preferably 7.0, 6.7, 6.5, 6.3, 6.1, 6.0, 5.9, 5.8, 5.5, 5.3, 5.0, 4.8, and 4.5. That is, the more preferred range of pH value is set according to the above upper and lower limits, for example, 1.5 or higher and 7.3 or lower, and most preferably 3.9 or higher and 4.5 or lower. In this invention, sometimes even without adding a pH adjuster before adding the iron raw material, the pH falls within the above-mentioned range; however, the essence of this invention is to add a pH adjuster before adding the iron raw material to adjust the pH to the above-mentioned range.
[0109] Regarding pH adjusters, in methods for lowering pH, in addition to acids commonly used for pH adjustment by those skilled in the art as catalyst raw materials, such as nitric acid, sulfuric acid, hydrochloric acid, and oxalic acid, pH adjusters containing residual elements after calcination, such as phosphoric acid, boric acid, molybdic acid, and ferric nitrate, are also included, provided that the elemental composition of the catalyst active components described later is not altered. However, nitric acid is the most preferred. In methods for raising pH, in addition to bases commonly used for pH adjustment by those skilled in the art as catalyst raw materials, such as ammonia, pyridine, and ammonium carbonate aqueous solutions, pH adjusters containing residual elements after calcination, such as potassium hydroxide and cesium hydroxide, are also included, provided that the elemental composition of the catalyst active components described later is not altered. However, ammonia is the most preferred.
[0110] Furthermore, in implementing this method, the preferred embodiment is a method of preparing a slurry by adding the bismuth raw material to the mixing solution in the order of adding the iron raw material and stirring.
[0111] When adding the pH adjuster, at a rate of 0.01 kW / m 3 ~5.00kw / m 3 The stirring power is added simultaneously during stirring, and the lower limit of the stirring power is preferably 0.05 kW / m³. 3 0.10kw / m 3 0.50kw / m3 1.00kw / m 3 The upper limit for stirring power is preferably 4.50 kW / m³. 3 4.00kw / m 3 3.50kw / m 3 3.00kw / m 3 That is, the optimal stirring power range is 1.00 kW / m³. 3 ~3.00kw / m 3 .
[0112] Regarding the addition time of the pH adjuster, the lower limit of the addition time is between 1 second and 5 minutes, preferably 5 seconds, 10 seconds, or 15 seconds, and the upper limit is preferably 4 minutes, 3 minutes, 2 minutes 30 seconds, 2 minutes, 1 minute 30 seconds, 1 minute, 45 seconds, or 30 seconds. That is, the most preferred addition time range is 15 seconds to 30 seconds.
[0113] The liquid temperature of the preparation solution when adding the pH adjuster is 5℃ to 80℃. The lower limit of the liquid temperature is preferably 10℃, 20℃, or 30℃, and the upper limit is preferably 70℃, 60℃, 50℃, or 40℃. That is, the most preferred range for the liquid temperature is 30℃ to 40℃.
[0114] <(b) Process>
[0115] In step (b), the slurry obtained in step (a) is dried. There are no particular limitations on the drying method, as long as it can completely dry the slurry; examples include drum drying, freeze drying, spray drying, and evaporative drying. In this invention, spray drying, which can dry the slurry into powder or granules in a short time, is particularly preferred. The drying temperature of the spray dryer varies depending on the slurry concentration, liquid delivery rate, etc., and the temperature at the dryer outlet is approximately 70°C or higher and approximately 150°C or lower.
[0116] <(c) Process>
[0117] In step (c), the dried slurry obtained in step (b) is shaped. It should be noted that, although not essential, calcination can be performed before shaping. In this specification, the calcination before shaping is referred to as pre-calcination.
[0118] Molding can be achieved using either supported molding on a support such as silica or unsupported molding without a support. Specific molding methods include, for example, tableting, compression molding, extrusion molding, and granulation. The shape of the molded product can be appropriately selected based on operating conditions, such as cylindrical, annular, or spherical shapes. The catalyst can be supported on a spherical support, particularly an inert support such as silica or alumina, with an average particle size of 3.0 mm or more and 10.0 mm or less, preferably 3.0 mm or more and 8.0 mm or less. Supporting methods such as rotary granulation, centrifugal flow coating, and wash coating are widely known. There are no particular limitations as long as the method can uniformly load the pre-calcined powder onto the support; however, rotary granulation is preferred when considering catalyst manufacturing efficiency. Specifically, the method is as follows: In a device with a flat or convex disc at the bottom of a fixed cylindrical container, the disc is rotated at high speed. This vigorously agitates the carrier within the container through repeated rotation and revolution, and pre-calcined powder is added, thereby loading the powder components onto the carrier. It should be noted that a binder is preferably used during loading. Specific examples of usable binders include: water, ethanol, methanol, propanol, polyols, polyvinyl alcohol as a polymer binder, and silica sol aqueous solutions as inorganic binders. Ethanol, methanol, propanol, and polyols are preferred; diols such as ethylene glycol and triols such as glycerol are more preferred; and aqueous solutions with a glycerol concentration of 5% by mass or more are even more preferred. By using an appropriate amount of aqueous glycerol solution, good formability is achieved, resulting in a catalyst with high mechanical strength and high performance. The amount of these binders used is typically 2 to 60 parts by mass relative to 100 parts by mass of pre-calcined powder, and preferably 15 to 50 parts by mass in the case of an aqueous glycerol solution. Under load, the binder and pre-calcined powder can be fed alternately or simultaneously into the molding machine. Additionally, small amounts of known additives such as graphite and talc can be added during molding. It should be noted that molding aids, pore-forming agents, and carriers added during molding are not considered as constituent elements of the active ingredients in this invention, regardless of whether they have any activity in the sense of converting the raw materials into some other product.
[0119] <(d) Process>
[0120] In step (d), the dried body or catalyst-coated body obtained in step (c) from step (b) is calcined. It should be noted that in this specification, step (d) is referred to as formal calcination.
[0121] The dried body or coated catalyst can be directly used as a catalyst for gas-phase catalytic oxidation reactions. However, considering that calcination would stabilize the structure and improve the catalyst performance, formal calcination is preferred.
[0122] There are no particular limitations on the pre-calcination method, pre-calcination conditions, or formal calcination method and conditions; known processing methods and conditions can be applied. Pre-calcination and formal calcination are typically carried out at a temperature of 200°C to 600°C, preferably 300°C to 550°C, for at least 0.5 hours, preferably 1 hour to 40 hours, under the flow of oxygen-containing gases such as air or inactive gases. Here, inactive gases refer to gases that do not reduce the reactivity of the catalyst; specifically, examples include nitrogen, carbon dioxide, helium, and argon. It should be noted that the process parameters for the formal calcination process, such as the oxygen content in the atmosphere, the maximum temperature reached, and the calcination time, can vary depending on the reaction conditions used in the production of unsaturated aldehydes and / or unsaturated carboxylic acids, particularly the optimal conditions in formal calcination. These variations are well known to those skilled in the art and therefore fall within the scope of this invention. Furthermore, the formal calcination process is carried out after the aforementioned pre-calcination process, and the highest temperature reached in the formal calcination process (formal calcination temperature) is higher than the highest temperature reached in the aforementioned pre-calcination process (pre-calcination temperature). The calcination method is not specifically limited to fluidized bed, rotary kiln, muffle furnace, tunnel furnace, etc.; an appropriate range should be selected considering the final catalyst performance, mechanical strength, formability, and production efficiency.
[0123] The catalyst of the present invention is preferably used as a catalyst for the production of unsaturated aldehyde compounds and unsaturated carboxylic acid compounds, more preferably as a catalyst for the production of unsaturated aldehyde compounds, and particularly preferably as a catalyst for the production of acrolein from propylene. In processes for the production of exothermic reactions such as unsaturated aldehyde compounds and unsaturated carboxylic acid compounds, it is well known to those skilled in the art that, in order to prevent the catalyst itself from deteriorating due to the exothermic reaction in actual plant equipment, multiple layers of different types of catalyst are filled in such a manner that the activity increases from the inlet side to the outlet side of the reaction tube. The catalyst of the present invention can be used in any of the catalyst layers at the inlet side and outlet side of the reaction tube, and most preferably in the catalyst layer closest to the outlet side of the reaction tube, i.e., the catalyst with the highest activity among all the catalyst layers in the reaction tube. It should be noted that, in multilayer packing, filling two or three layers is particularly preferred. Furthermore, the catalyst used as a catalyst for the manufacture of unsaturated aldehyde compounds and unsaturated carboxylic acid compounds is also suitable for the manufacture of conjugated dienes from monoolefin feedstocks with 4 or more carbon atoms via oxidative dehydrogenation reactions. Specifically, it is a catalyst for the manufacture of butadiene from n-butene feedstocks via oxidative dehydrogenation reactions. This is well known to those skilled in the art, and such a method of use is also possible.
[0124] [Adjustment methods for R1, R2, and R3]
[0125] The values of R1, R2, and R3 can be controlled by the pH adjustment method described in step (a). In addition, they can be controlled by, for example, by (I) changing the catalyst composition, (II) changing the calcination conditions, (III) changing the cooling conditions after calcination, (IV) controlling the catalyst and its precursors in a manner that does not apply mechanical strength in all steps of catalyst manufacturing, (V) using high-purity raw materials, other methods (VI) to (VIII), and combinations of (I) to (VIII).
[0126] <Method (I)>
[0127] Regarding method (I), methods for changing the composition of the catalyst in the above formula (I) in the following ways can be listed.
[0128] The upper limit of e1 / b1 is 3.30, preferably 3.00, and the lower limit of e1 / b1 is preferably 0.10, 0.50, 1.00, 1.40, and 1.50 respectively. The preferred upper limits for d1 / b1 are 9.5, 9.0, 8.5, and 8.0, respectively; the preferred lower limits for d1 / b1 are 2.0, 3.0, 4.0, 5.0, and 5.5, respectively. The preferred upper limits for c1 / e1 are 4.0, 3.0, and 2.5, respectively; the preferred lower limits for c1 / e1 are 1.0, 1.1, and 1.2, respectively. The upper limit of c1 / d1 is preferably 2.0, 1.0, and 0.8, respectively; the lower limit of c1 / d1 is preferably 0.3 and 0.4, respectively. The upper limit of g1 / d1 is preferably 0.10, 0.05, 0.04, and 0.03, respectively, and the lower limit of g1 / d1 is 0.01. The upper limit of g1 / c1 is preferably 0.041 and 0.039, respectively, and the lower limit of g1 / c1 is preferably 0.020, 0.025 and 0.027, respectively.
[0129] <Method (II)>
[0130] Regarding method (II), the following methods can be used to change the calcination conditions: in pre-calcination and formal calcination, and in both, the following conditions are set: 200°C or higher and 600°C or lower, preferably 300°C or higher and 550°C or lower, more preferably 460°C or higher and 550°C or lower; 0.5 hours or higher, preferably 1 hour or higher and 40 hours or lower, more preferably 2 hours or higher and 15 hours or lower, most preferably 2 hours or higher and 9 hours or lower; and as the atmosphere, the oxygen concentration is 10% by volume or higher and 40% by volume or lower, preferably 15% by volume or higher and 30% by volume or lower, and most preferably an air atmosphere.
[0131] <Method (III)>
[0132] Regarding method (III), methods for altering the cooling conditions after calcination can be listed as follows: In pre-calcination and formal calcination, and both, the rate of temperature reduction (cooling rate) from the highest temperature reached in the calcination process (pre-calcination temperature or formal calcination temperature) to the temperature of the catalyst surface at room temperature is 1°C / min or more and 200°C / min or less, preferably 5°C / min or more and 150°C / min or less, more preferably 10°C / min or more and 120°C / min or less, and most preferably 50°C / min or more and 100°C / min or less. Cooling methods commonly used industrially to achieve the above-mentioned cooling rate range, such as methods of exposing the catalyst taken from the calcination furnace to a mist generated by an inactive atmosphere or inert solvent, and methods of rapidly transferring the catalyst to a pre-cooled chamber, all fall within the scope of this embodiment.
[0133] <Method (IV)>
[0134] Regarding method (IV), it is a method of controlling the mechanical impact and shear stress, etc., of the catalyst precursor and / or particles formed in each process without applying them. The preferred range for the mechanical impact and shear stress, etc., is controlled to be 100 kgf or less, preferably 50 kgf or less, more preferably 20 kgf or less, further preferably 10 kgf or less, and most preferably 5 kgf or less.
[0135] <Method (V)>
[0136] Regarding method (V), there are no restrictions on the details of any method that uses reagent-grade high-purity raw materials. For example, a method can be listed in which the content of sulfur and its compounds, lithium, halogens and their compounds, and lead is 10,000 ppm by weight or less, preferably 1,000 ppm by weight or less, more preferably 100 ppm by weight or less, and most preferably 10 ppm by weight or less.
[0137] <Method (VI)>
[0138] Regarding method (VI), one approach is to first obtain the catalyst precursor in particulate form and then shape it. By obtaining the catalyst precursor in particulate form, the components of the catalyst can be manufactured more uniformly.
[0139] <Method (VII)>
[0140] Regarding method (VII), it is a method for controlling the mixing, reaction, slurry formation, and residence time of cobalt and nickel raw materials in the mixing vessel during the catalyst preparation process, in order to minimize these times. More specifically, it is a method for shortening the residence time when cobalt and nickel raw materials are present in the mixing vessel but no metal salt raw materials other than molybdenum and alkali metals are present; or a method for shortening the residence time when cobalt and nickel raw materials are present in the mixing vessel when the pH in the mixing vessel is within a specific range. The residence time is preferably 24 hours, more preferably 1 hour, more preferably 30 minutes, and most preferably 10 minutes. The pH range is 1 or more and 14 or less, preferably 2 or more and 10 or less, more preferably 2 or more and 8 or less, and most preferably 3 or more and 7 or less. The same applies to iron and bismuth raw materials, and molybdenum and bismuth raw materials.
[0141] <Method (VIII)>
[0142] Regarding method (VIII), examples can be given in the catalyst preparation process described later, such as a method of adding all raw materials at once without batches during the preparation process; or a method of reducing the nitric acid concentration in the preparation solution. The aforementioned method of adding all raw materials at once means adding the necessary amount of each raw material before adding the next. Furthermore, regarding the nitric acid concentration in the preparation solution, the concentration of nitrate ions in the preparation solution entering the next process after preparation is preferably 40% by mass or less, more preferably 35% by mass or less, further preferably 30% by mass or less, and most preferably 25% by mass or less.
[0143] <Regarding the catalyst in the second paragraph>
[0144] When the catalyst of the present invention is used as the catalyst for the first stage, i.e., for the production of unsaturated aldehyde compounds, the second stage of oxidation reaction can be carried out to obtain unsaturated carboxylic acid compounds.
[0145] In this case, the catalyst of the present invention can also be used as the catalyst for the second stage, preferably a catalyst containing a catalytically active component represented by the following formula (II).
[0146] Mo 12 V a2 W b2 Cu c2 Sb d2 X2 e2 Y2 f2 Z2 g2 O h2 ...(II)
[0147] (In formula (II), Mo, V, W, Cu, Sb, and O represent molybdenum, vanadium, tungsten, copper, antimony, and oxygen, respectively; X2 represents at least one element selected from the group consisting of alkali metals and thallium; Y2 represents at least one element selected from the group consisting of magnesium, calcium, strontium, barium, and zinc; and Z2 represents at least one element selected from the group consisting of niobium, cerium, tin, chromium, manganese, iron, cobalt, samarium, germanium, titanium, and arsenic. Furthermore, a2, b2, c2, d2, e2, f2, g2, and h2 represent the atomic ratios of each element. Relative to 12 molybdenum atoms, a2 represents 0 < a2 ≤ 10, b2 represents 0 ≤ b2 ≤ 10, c2 represents 0 < c2 ≤ 6, d2 represents 0 < d2 ≤ 10, e2 represents 0 ≤ e2 ≤ 0.5, f2 represents 0 ≤ f2 ≤ 1, and g2 represents 0 ≤ g2 < 6. Additionally, h2 represents the number of oxygen atoms required to satisfy the valences of the above components.)
[0148] When manufacturing a catalyst containing the catalytic active component represented by formula (II) above, methods generally known for preparing such catalysts, such as oxide catalysts, catalysts having a structure of heteropolyacids or their salts, can be used. There are no particular limitations on the raw materials that can be used in manufacturing the catalyst; various raw materials can be used. For example, molybdenum oxides such as molybdenum trioxide; molybdic acids such as molybdic acid and ammonium molybdate or their salts; molybdenum-containing heteropolyacids such as phosphomolybdic acid and silicomolybdic acid or their salts can be used. There are no particular limitations on the antimony component raw material; antimony trioxide or antimony acetate are preferred. As raw materials for other elements such as vanadium, tungsten, and copper, their respective nitrates, sulfates, carbonates, phosphates, organic acid salts, halides, hydroxides, oxides, metals, etc., can be used. These compounds containing the active component can be used alone or in combination of two or more.
[0149] Next, the slurry obtained above is dried to produce a solid catalyst active ingredient. There are no particular limitations on the drying method as long as it can completely dry the slurry; examples include drum drying, freeze drying, spray drying, and evaporative drying. Spray drying, which can dry the slurry into powder or particles in a short time, is preferred. The drying temperature of spray drying varies depending on the slurry concentration and liquid delivery rate, and is typically around 70°C to around 150°C at the dryer outlet. Furthermore, drying is preferably carried out in a manner that results in an average particle size of 10 μm to 700 μm in the dried slurry.
[0150] The second-stage catalyst active component solid obtained in the above manner can be directly used in the coating mixture; however, calcination sometimes improves its formability, making it preferred. There are no particular restrictions on the calcination method or conditions; known processing methods and conditions can be used. The optimal calcination conditions vary depending on the catalyst raw materials, catalyst composition, and preparation method used. The calcination temperature is typically 100°C to 350°C, preferably 150°C to 300°C, and the calcination time is 1 hour to 20 hours. It should be noted that calcination is usually carried out in an air atmosphere, but it can also be carried out in an inactive gas atmosphere such as nitrogen, carbon dioxide, helium, or argon. Furthermore, calcination can be performed in an inactive gas atmosphere followed by further calcination in an air atmosphere as needed. The calcined solid obtained in this manner is preferably pulverized before molding. There are no particular restrictions on the pulverization method; a ball mill can be used.
[0151] In addition, the active ingredient compound used in preparing the slurry of the second stage does not necessarily need to contain all of the active ingredients; a portion of the ingredients can be used before the molding process described below.
[0152] There are no particular restrictions on the shape of the catalyst in the second paragraph above. In order to reduce the pressure loss of the reactant gas in the oxidation reaction, it can be shaped into columnar, tablet, ring, spherical, etc. and used. Among these, considering the potential for improved selectivity and removal of reaction heat, it is particularly preferred to prepare a supported catalyst by loading the solid active catalyst component onto an inert support. This loading is preferably carried out by the rotary granulation method described below. This method is, for example, as follows: in a device having a flat or uneven disc at the bottom in a fixed container, the disc is rotated at high speed, thereby vigorously agitating the support in the container by repeated rotation and revolution. A binder and solid active catalyst component are added to it, and other additives such as molding aids and strength enhancers are added as needed. The resulting loading is then loaded onto the support with the mixture. The binder can be added in any of the following ways: 1) pre-mixed in the above-mentioned load mixture; 2) added simultaneously with adding the load mixture to the fixed container; 3) added after adding the load mixture to the fixed container; 4) added before adding the load mixture to the fixed container; 5) adding the load mixture and binder in batches and appropriately combined according to methods 2) to 4) to add the total amount. In method 5), it is preferable to use an automatic feeder or similar device to adjust the addition speed so as to load a predetermined amount onto the carrier without causing, for example, adhesion of the load mixture to the wall of the fixed container or aggregation of the load mixture. Examples of binders include: water; ethanol; polyols; polyvinyl alcohol as a polymer binder; cellulose-based binders such as crystalline cellulose, methylcellulose, and ethylcellulose; and aqueous solutions of silica sol as inorganic binders. Cellulose-based binders and diols such as ethylene glycol and triols such as glycerol are preferred, and aqueous solutions of glycerol with a concentration of 5% by mass or more are particularly preferred. The amount of these adhesives used is typically 2 to 60 parts by weight, preferably 10 to 50 parts by weight, relative to 100 parts by weight of the load-bearing mixture.
[0153] Specific examples of supports for the aforementioned loading include spherical supports with diameters of 1 mm to 15 mm, preferably 2.5 mm to 10 mm, such as silicon carbide, alumina, silica-alumina, mullite, and alumina. Supports with a porosity of 10% to 70% are typically used for these supports. The ratio of the support to the loading mixture is typically 10% to 75% by mass, preferably 15% to 60% by mass, where the ratio of loading mixture to (loading mixture + support) is 10% to 75% by mass. A higher proportion of the loading mixture increases the reactivity of the supported catalyst but tends to decrease its mechanical strength. Conversely, a lower proportion of the loading mixture increases mechanical strength but tends to decrease reactivity. It should be noted that, as molding aids used as needed, examples include silica gel, diatomaceous earth, and alumina powder. The amount of molding aid used is typically 1 to 60 parts by mass relative to 100 parts by mass of the catalyst active ingredient solid. Furthermore, inorganic fibers (e.g., ceramic fibers or whiskers) that are inert to both the solid active catalyst component and the reactant gas can be used as strength enhancers, which is useful for improving the mechanical strength of the catalyst; glass fibers are preferred. The amount of these fibers used is typically 1 to 30 parts by mass relative to 100 parts by mass of the solid active catalyst component. It should be noted that in the catalyst forming process of the first stage, regardless of whether there is any activity in the sense of converting the raw material into some other product, the added forming aids, pore-forming agents, and supports are not considered as constituent elements of the active component in this invention.
[0154] The supported catalyst obtained in the above manner can be directly used as a catalyst for gas-phase catalytic oxidation reactions. However, calcination can sometimes improve catalyst activity, making it a preferred method. There are no particular restrictions on the calcination method or conditions; known processing methods and conditions can be applied. The optimal calcination conditions vary depending on the catalyst raw materials, catalyst composition, and preparation method used. The calcination temperature is typically 100℃ to 450℃, preferably 270℃ to 420℃, and the calcination time is 1 hour to 20 hours. It should be noted that calcination is usually carried out in an air atmosphere, but it can also be carried out in an inert gas atmosphere such as nitrogen, carbon dioxide, helium, or argon. Furthermore, calcination can be performed in an inert gas atmosphere followed by further calcination in an air atmosphere as needed.
[0155] When the catalyst of the present invention is used in reactions to produce corresponding unsaturated aldehydes and unsaturated carboxylic acids from propylene, isobutylene, tert-butanol, etc., particularly in the gas-phase catalytic oxidation of propylene using molecular oxygen or oxygen-containing gases to produce acrolein and acrylic acid, the catalyst activity and yield can be improved. Compared with known methods, this is highly effective in improving the price competitiveness of the products. Furthermore, it is expected to improve the process stability of exothermic partial oxidation reactions, such as reducing the hotspot temperature. In addition, the catalyst of the present invention is also effective in reducing byproducts that adversely affect the environment and the quality of the final product, such as carbon monoxide (CO), carbon dioxide (CO2), acetaldehyde, acetic acid, and formaldehyde.
[0156] The catalyst of the present invention obtained in this manner can, for example, be used to produce acrolein and / or acrylic acid by gas-phase catalytic oxidation of propylene using a gas containing molecular oxygen. In the manufacturing method of the present invention, the flow method of the raw material gas can be a conventional one-way flow method or a recirculation method, which can be implemented under normal operating conditions without particular limitation. For example, a mixture of inactive gases including propylene (at room temperature 1% to 10% by volume, preferably 4% to 9% by volume); molecular oxygen (3% to 20% by volume, preferably 4% to 18% by volume); water vapor (0% to 60% by volume, preferably 4% to 50% by volume); carbon dioxide (20% to 80% by volume, preferably 30% to 60% by volume); and nitrogen (20% to 80% by volume, preferably 30% to 60% by volume) is subjected to a pressure of atmospheric pressure to 10 atmospheres for 300 hours at 250°C to 450°C. -1 ~5000 hours -1 The space velocity is introduced onto the catalyst of the present invention, which is filled in the reaction tube, and the reaction takes place.
[0157] In this invention, unless otherwise stated, improved catalyst activity refers to a higher feed conversion rate when the catalytic reaction is carried out at the same reaction bath temperature and compared.
[0158] In this invention, unless otherwise stated, "high yield" means a high total yield of the corresponding unsaturated aldehydes and / or unsaturated carboxylic acids when the oxidation reaction is carried out using propylene, isobutylene, tert-butanol, etc. as raw materials. Furthermore, unless otherwise stated, "yield" refers to the effective yield described later.
[0159] In this invention, unless otherwise stated, the constituent elements of the catalyst active component refer to all elements used in the above-described catalyst manufacturing process. However, raw materials and their constituent elements that disappear, sublimate, volatilize, or burn at temperatures below the highest temperature of the formal calcination process are not included in the constituent elements of the catalyst active component. Furthermore, molding aids in the molding process, silicon contained in the carrier, and elements constituting other inorganic materials are also not included in the constituent elements of the catalyst active component.
[0160] In this invention, the hot spot temperature refers to the highest temperature of the temperature distribution within the catalyst packing layer measured by thermocouples placed along the long axis of the multi-tube reaction tube, and the reaction bath temperature refers to the set temperature of the heat medium used to cool the exothermic reaction tube. There is no particular limitation on the number of measurement points for the above temperature distribution; for example, the catalyst packing length can be evenly divided into 10 to 1000 sections.
[0161] In this invention, unsaturated aldehydes and unsaturated aldehyde compounds refer to organic compounds having at least one double bond and at least one aldehyde group within the molecule, such as acrolein and methacrolein. In this invention, unsaturated carboxylic acids and unsaturated carboxylic acid compounds refer to organic compounds having at least one double bond and at least one carboxyl group or ester group within the molecule, such as acrylic acid, methacrylic acid, and methyl methacrylate. In this invention, conjugated dienes refer to dienes in which the double bonds are separated by a single bond and are chemically conjugated, such as 1,3-butadiene.
[0162] The method for manufacturing the catalyst of the present invention is simpler than that for existing catalysts, thus enabling the production of high-performance catalysts despite low manufacturing costs. Furthermore, the catalyst of the present invention can effectively improve yields even in regions of low catalyst activity. In addition, improvements can be observed in the process stability of exothermic partial oxidation reactions, such as a decrease in ΔT (the difference between the hot spot temperature and the reaction bath temperature).
[0163] Example
[0164] The present invention will be described in more detail below through embodiments. It should be noted that, in the embodiments, the raw material conversion rate, effective yield, effective selectivity, and loading rate are calculated according to the following formulas.
[0165] Feed conversion rate (%) = (moles of propylene that reacted) / (moles of propylene supplied) × 100
[0166] Effective yield (%) = (Total moles of acrolein and acrylic acid produced) / (Moles of propylene supplied) × 100
[0167] Effective selectivity (%) = (Total moles of acrolein and acrylic acid produced) / (Moles of propylene that reacted) × 100
[0168] Loading rate (mass%) = (mass of pre-calcined powder used in molding) / {(mass of pre-calcined powder used in molding) + (mass of carrier used in molding)} × 100
[0169] [Example 1]
[0170] 100 parts by weight of ammonium heptamolybdate were completely dissolved in 380 parts by weight of pure water heated to 60°C (mother liquor 1). Next, 0.22 parts by weight of potassium nitrate were dissolved in 1.9 parts by weight of pure water and added to mother liquor 1. Then, 9.3 parts by weight of nitric acid (60% by weight) were added to adjust the pH to 4. Next, 38 parts by weight of ferric nitrate, 91 parts by weight of cobalt nitrate, and 30 parts by weight of nickel nitrate were dissolved in 84 parts by weight of pure water heated to 60°C and added to mother liquor 1. Next, 4.1 parts by weight of nitric acid (60% by weight) was added to 17 parts by weight of pure water heated to 60°C to prepare an aqueous nitric acid solution. 16 parts by weight of bismuth nitrate were dissolved in the aqueous nitric acid solution and added to mother liquor 1. Mother liquor 1 was dried by spray drying, and the resulting dried powder was pre-calcined at 440°C for 4 hours. 5% by mass of crystalline cellulose was added to the pre-calcined powder obtained therefrom (the atomic ratio calculated from the input raw materials was Mo:Bi:Fe:Co:Ni:K = 12:0.7:2.0:6.6:2.2:0.05), and the mixture was thoroughly mixed. Then, the powder was granulated on an inert support using a 33% by mass glycerol solution as a binder to achieve a loading rate of 50% by mass, and spherical shapes were formed. The resulting spherical shapes with a particle size of 5.3 mm were then formally calcined at 530°C for 4 hours to obtain catalyst 1.
[0171] [Example 2]
[0172] 100 parts by weight of ammonium heptamolybdate were completely dissolved in 380 parts by weight of pure water heated to 60°C (mother liquor 1). Next, 0.27 parts by weight of potassium nitrate were dissolved in 2.4 parts by weight of pure water and added to mother liquor 1. Then, 19.3 parts by weight of ammonia (10% by weight) were added to adjust the pH to 6. Next, 44 parts by weight of ferric nitrate, 89 parts by weight of cobalt nitrate, and 32 parts by weight of nickel nitrate were dissolved in 87 parts by weight of pure water heated to 60°C and added to mother liquor 1. Next, 4.1 parts by weight of nitric acid (60% by weight) was added to 17 parts by weight of pure water heated to 60°C to prepare an aqueous nitric acid solution. 16 parts by weight of bismuth nitrate were dissolved in the aqueous nitric acid solution and added to mother liquor 1. Mother liquor 1 was dried by spray drying, and the resulting dried powder was pre-calcined at 440°C for 4 hours. 5% by mass of crystalline cellulose was added to the pre-calcined powder obtained therefrom (the atomic ratio calculated from the input raw materials was Mo:Bi:Fe:Co:Ni:K = 12:0.7:2.3:6.5:2.3:0.06), and the mixture was thoroughly mixed. Then, the powder was granulated on an inert support using a 33% by mass glycerol solution as a binder to achieve a loading rate of 50% by mass, thus forming spherical particles. The resulting spherical particles with a particle size of 5.3 mm were then formally calcined at 530°C for 4 hours to obtain catalyst 2.
[0173] [Example 3]
[0174] 100 parts by weight of ammonium heptamolybdate were completely dissolved in 380 parts by weight of pure water heated to 60°C (mother liquor 1). Next, 0.42 parts by weight of potassium nitrate were dissolved in 3.8 parts by weight of pure water and added to mother liquor 1. Then, 10.6 parts by weight of nitric acid (60% by weight) were added to adjust the pH to 4. Next, 38 parts by weight of ferric nitrate, 82 parts by weight of cobalt nitrate, and 40 parts by weight of nickel nitrate were dissolved in 85 parts by weight of pure water heated to 60°C and added to mother liquor 1. Next, 4.4 parts by weight of nitric acid (60% by weight) was added to 18 parts by weight of pure water heated to 60°C to prepare an aqueous nitric acid solution. 17 parts by weight of bismuth nitrate were dissolved in the aqueous nitric acid solution and added to mother liquor 1. Mother liquor 1 was dried by spray drying, and the resulting dried powder was pre-calcined at 440°C for 4 hours. 5% by mass of crystalline cellulose was added to the pre-calcined powder obtained therefrom (the atomic ratio calculated from the input raw materials was Mo:Bi:Fe:Co:Ni:K = 12:0.8:2.0:6.0:2.9:0.09), and the mixture was thoroughly mixed. Then, the powder was granulated on an inert support using a 33% by mass glycerol solution as a binder to achieve a loading rate of 50% by mass, thus forming spherical particles. The resulting spherical particles with a particle size of 5.3 mm were then formally calcined at 530°C for 4 hours to obtain catalyst 3.
[0175] [Example 4]
[0176] 100 parts by weight of ammonium heptamolybdate were completely dissolved in 380 parts by weight of pure water heated to 60°C (mother liquor 1). Next, 0.31 parts by weight of potassium nitrate were dissolved in 2.9 parts by weight of pure water and added to mother liquor 1. Then, 10.6 parts by weight of nitric acid (60% by weight) were added to adjust the pH to 4. Next, 35 parts by weight of ferric nitrate, 84 parts by weight of cobalt nitrate, and 36 parts by weight of nickel nitrate were dissolved in 82 parts by weight of pure water heated to 60°C and added to mother liquor 1. Next, 4.4 parts by weight of nitric acid (60% by weight) was added to 18 parts by weight of pure water heated to 60°C to prepare an aqueous nitric acid solution. 17 parts by weight of bismuth nitrate were dissolved in the aqueous nitric acid solution and added to mother liquor 1. Mother liquor 1 was dried by spray drying, and the resulting dried powder was pre-calcined at 440°C for 4 hours. 5% by mass of crystalline cellulose was added to the pre-calcined powder obtained therefrom (the atomic ratio calculated from the input raw materials was Mo:Bi:Fe:Co:Ni:K = 12:0.8:1.9:6.1:2.6:0.07), and the mixture was thoroughly mixed. Then, the powder was granulated on an inert support using a 33% by mass glycerol solution as a binder to achieve a loading rate of 50% by mass, and spherical shapes were formed. The resulting spherical shapes with a particle size of 5.3 mm were then formally calcined at 520°C for 4 hours to obtain catalyst 4.
[0177] [Comparative Example 1]
[0178] 100 parts by weight of ammonium heptamolybdate were completely dissolved in 380 parts by weight of pure water heated to 60°C (mother liquor 1). Next, 0.17 parts by weight of potassium nitrate were dissolved in 1.9 parts by weight of pure water and added to mother liquor 1. The pH of mother liquor 1 at this point was 5.2. Next, 41 parts by weight of ferric nitrate, 89 parts by weight of cobalt nitrate, and 33 parts by weight of nickel nitrate were dissolved in 85 parts by weight of pure water heated to 60°C and added to mother liquor 1. Next, 4.1 parts by weight of nitric acid (60% by weight) was added to 17 parts by weight of pure water heated to 60°C to prepare an aqueous nitric acid solution. 16 parts by weight of bismuth nitrate were dissolved in the aqueous nitric acid solution and added to mother liquor 1. Mother liquor 1 was dried by spray drying, and the resulting dried powder was pre-calcined at 440°C for 4 hours. 5% by mass of crystalline cellulose was added to the pre-calcined powder obtained therefrom (the atomic ratio calculated from the input raw materials was Mo:Bi:Fe:Co:Ni:K = 12:0.7:2.2:6.5:2.4:0.04), and the mixture was thoroughly mixed. Then, the mixture was granulated on an inert support using a 33% by mass glycerol solution as a binder to achieve a loading rate of 50% by mass, forming spherical shapes. The resulting spherical shapes with a particle size of 5.3 mm were then formally calcined at 550°C for 4 hours to obtain catalyst 5.
[0179] [Reference Example 1]
[0180] 100 parts by weight of ammonium heptamolybdate were completely dissolved in 380 parts by weight of pure water heated to 60°C (mother liquor 1). Next, 0.45 parts by weight of potassium nitrate were dissolved in 45 parts by weight of pure water and added to mother liquor 1. Then, 38 parts by weight of ferric nitrate, 71 parts by weight of cobalt nitrate, and 38 parts by weight of nickel nitrate were dissolved in 76 parts by weight of pure water heated to 60°C and added to mother liquor 1. Next, 9.7 parts by weight of nitric acid (60% by weight) was added to 41 parts by weight of pure water heated to 60°C to prepare an aqueous nitric acid solution. 36 parts by weight of bismuth nitrate were dissolved in the aqueous nitric acid solution and added to mother liquor 1. Mother liquor 1 was dried by spray drying, and the resulting dried powder was pre-calcined at 440°C for 4 hours. 5% by mass of crystalline cellulose was added to the pre-calcined powder obtained therefrom (the atomic ratio calculated from the input raw materials was Mo:Bi:Fe:Co:Ni:K = 12:1.6:2.0:5.2:2.8:0.10), and the mixture was thoroughly mixed. Then, the mixture was granulated on an inert support using a 33% by mass glycerol solution as a binder to achieve a loading rate of 50% by mass, forming spherical shapes. The resulting spherical shapes with a particle size of 5.3 mm were then formally calcined at 530°C for 4 hours to obtain catalyst 6.
[0181] [Comparative Example 2]
[0182] 100 parts by weight of ammonium heptamolybdate were completely dissolved in 380 parts by weight of pure water heated to 60°C (mother liquor 1). Next, 0.17 parts by weight of potassium nitrate were dissolved in 1.9 parts by weight of pure water and added to mother liquor 1. Next, 89 parts by weight of cobalt nitrate and 33 parts by weight of nickel nitrate were dissolved in 73 parts by weight of pure water heated to 60°C and added to mother liquor 1. Next, 1.2 parts by weight of nitric acid (60% by weight) was added to adjust the pH to 3.0. Next, 6.5 parts by weight of nitric acid (60% by weight) was added to 36 parts by weight of pure water heated to 60°C to prepare an aqueous nitric acid solution. 16 parts by weight of bismuth nitrate and 41 parts by weight of ferric nitrate were dissolved in the aqueous nitric acid solution and added to mother liquor 1. Mother liquor 1 was dried by spray drying, and the resulting dried powder was pre-calcined at 440°C for 4 hours. 5% by mass of crystalline cellulose was added to the pre-calcined powder obtained therefrom (the atomic ratio calculated from the input raw materials was Mo:Bi:Fe:Co:Ni:K = 12:0.7:2.2:6.5:2.4:0.04), and the mixture was thoroughly mixed. Then, the powder was granulated on an inert support using a rotary granulation method with a 33% by mass glycerol solution as a binder to achieve a loading rate of 50% by mass, forming spherical shapes. The resulting spherical shapes with a particle size of 5.3 mm were then formally calcined at 530°C for 4 hours to obtain catalyst 7.
[0183] [Comparative Example 3]
[0184] 100 parts by weight of ammonium heptamolybdate were completely dissolved in 380 parts by weight of pure water heated to 60°C (mother liquor 1). Next, 0.17 parts by weight of potassium nitrate were dissolved in 1.9 parts by weight of pure water and added to mother liquor 1. Then, 100.0 parts by weight of 28% ammonia solution was added to adjust the pH to 6.15. Next, 89 parts by weight of cobalt nitrate and 33 parts by weight of nickel nitrate were dissolved in 73 parts by weight of pure water heated to 60°C and added to mother liquor 1. Next, 4.1 parts by weight of nitric acid (60% by weight) was added to 17 parts by weight of pure water heated to 60°C to prepare an aqueous nitric acid solution, and 16 parts by weight of bismuth nitrate were dissolved in the aqueous nitric acid solution and added to mother liquor 1. Finally, 41 parts by weight of ferric nitrate were dissolved in 160 parts by weight of pure water heated to 60°C and added to mother liquor 1. The mother liquor 1 was dried by spray drying, and the resulting dried powder was pre-calcined at 440°C for 4 hours. 5% by mass of crystalline cellulose was added to the pre-calcined powder (the atomic ratio calculated from the input raw materials was Mo:Bi:Fe:Co:Ni:K = 12:0.7:2.2:6.5:2.4:0.04), and the mixture was thoroughly mixed. Then, the mixture was rotated onto an inert support and sphericalized using a 33% by mass glycerol solution as a binder to achieve a loading rate of 50% by mass. The resulting spherical particles with a diameter of 5.3 mm were then formally calcined at 530°C for 4 hours to obtain catalyst 8.
[0185] Propylene oxidation was carried out using catalysts 1 to 5, 7, and 8 as follows, and the feed conversion and effective yield were determined. Catalyst 6 was packed at the gas inlet side of a 28 mm inner diameter stainless steel reaction tube, and catalysts 1 to 5, 7, and 8 were packed at the gas outlet side. The propylene space velocity was set at 100 h⁻¹ relative to the total catalyst volume in the reaction tube. -1 A mixed gas with a volume ratio of propylene:oxygen:water vapor:nitrogen = 1.00:1.65:1.27:9.53 was introduced, and the oxidation reaction of propylene was carried out. The aging reaction was carried out at a reaction bath temperature of 315°C for more than 20 hours from the start of the reaction. The feed conversion rate and effective yield, as shown in Table 1, were then determined by analyzing the gas exiting the reaction tube at a reaction bath temperature of 320°C. Additionally, the Raman spectroscopy results are also shown in Table 1. It should be noted that the Raman spectrophotometry measurements of catalysts 1 to 5, 7, and 8 were performed according to the equipment and conditions illustrated above.
[0186] Table 1
[0187] Table 2
[0188] The naming rules for each Raman parameter in the table are as follows.
[0189] p- : Generate the first Peak position of the maximum value of each peak / cm -1
[0190] w- : No. Peak width per cm -1
[0191] i- :(No. (the maximum value of each peak) ÷ (354cm) -1 ±5cm -1 (the maximum value of the peak at that point)
[0192] In the above, with The corresponding peaks are assigned as follows: 0:354cm -1 ±5cm -1 peak 1: 782cm -1 ±5cm -1 peak 2: 820cm -1 ±5cm -1 peak 3: 868cm -1 ±5cm -1 peak 4: 886cm -1 ±5cm -1 peak 5: 900cm -1 ±5cm -1 peak 6: 940cm -1 ±4cm -1 peak 7: 952cm -1 ±7cm -1 peak 8: 968cm -1 ±5cm -1 peak 9:989cm -1 ±5cm -1 peak Additionally, R1 = i - 4, R2 = p - 7.
[0193] As shown in Table 1, catalysts 1 to 4, with R1, R2, and R3 within the scope of this invention, exhibit significantly high effective yields. Furthermore, the inventors have clarified that the effective yield is related to R1, R2, and R3 by a generally linear relationship: the more R1, R2, and R3 increase, the higher the effective yield becomes; from the viewpoint of effective yield, there exists a preferred range for these parameters.
[0194] Although the invention has been described in detail with reference to specific embodiments, various changes and modifications can be made without departing from the spirit and scope of the invention, which will be apparent to those skilled in the art.
[0195] It should be noted that this application is based on Japanese patent application filed on March 3, 2021 (Japanese Patent Application No. 2021-33249), the entire contents of which are incorporated herein by reference. Furthermore, all references cited herein are incorporated in their entirety.
[0196] Industrial practicality
[0197] By using the present invention, high yields can be obtained in the case of gas-phase oxidation reactions, especially in the case of producing unsaturated aldehyde compounds or unsaturated carboxylic acid compounds by partial oxidation reactions.
Claims
1. A catalyst, wherein, The composition of the active component of the catalyst is represented by formula (I) below, and the R1 of the catalyst represented by formula (I) below is 0.45 or more and 5.00 or less. Mo a1 Bi b1 Ni c1 Co d1 Feb e1 X f1 Y g1 Z h1 O i1 ……(I) In formula (I), Mo, Bi, Ni, Co, and Fe represent molybdenum, bismuth, nickel, cobalt, and iron, respectively; X refers to at least one element selected from tungsten, antimony, tin, zinc, chromium, manganese, magnesium, silicon, aluminum, cerium, and titanium; Y refers to potassium or cesium; Z refers to at least one element belonging to groups 1 to 16 of the periodic table and selected from elements other than Mo, Bi, Ni, Co, Fe, X, and Y; and a1, b1, c1, d1, e1, f1, g1, h1, and i1 represent molybdenum, bismuth, nickel, cobalt, and iron, respectively. The atomic numbers of cobalt, iron, X, Y, Z, and oxygen, when a1=12, are: 0.7≤b1≤1.1, 1.5≤c1≤3.2, 5.8≤d1≤7, 0<c1+d1≤20, 1.5≤e1≤2.0, 0≤f1≤2, 0.04≤g1≤0.10, 0≤h1≤5, 2.50≤e1 / b1≤3.30, 5.5≤d1 / b1≤8.5, 0.020≤g1 / c1≤0.039, and i1 = a value determined by the oxidation state of each element. R1 = (886 cm⁻¹) determined by Raman spectroscopy -1 ±5cm -1 (maximum value of the peak at 354cm) ÷ (354cm) -1 ±5cm -1 (the maximum value of the peak at that point)……(1), Here, the Raman spectroscopy measurements were performed under the following conditions: excitation laser wavelength of 785 nm, laser power of 240 mW to 480 mW, laser irradiation time of 50 ms, and a cumulative number of 64 measurements. The maximum value of the peak was obtained by fitting the measured data with a Gaussian function (Equation (4)) and performing peak separation processing. y=(i’- )×exp{-(x-(p- )) 2 ÷(w- ) 2 }……(4) Where y: Gaussian function (wavenumber x / cm) -1 (function) p- : Generate the first Peak position of the maximum value of each peak / cm -1 w- : No. Peak width per cm -1 i'- :(No. (the maximum value of each peak) i- :(No. (the maximum value of each peak) ÷ (354cm) -1 ±5cm -1 (the maximum value of the peak at that point) exp: an exponential function with base e. In the above, with The corresponding peak assignments are as follows. 0:354cm -1 ±5cm -1 peak 1: 782cm -1 ±5cm -1 peak 2: 820cm -1 ±5cm -1 peak 3: 868cm -1 ±5cm -1 peak 4: 886cm -1 ±5cm -1 peak 5: 900cm -1 ±5cm -1 peak 6: 940cm -1 ±4cm -1 peak 7: 952cm -1 ±7cm -1 peak 8: 968cm -1 ±5cm -1 peak 9:989cm -1 ±5cm -1 The peak.
2. The catalyst as claimed in claim 1, wherein, The catalyst has an R² value of 951.4 cm², as expressed by formula (2). -1 Above and 959.0cm -1 the following, R2 = produces 952 cm⁻¹ as determined by Raman spectroscopy. -1 ±7cm -1 wavenumber of the peak at the maximum value / cm -1 ……(2).
3. The catalyst as described in claim 1, wherein, The catalyst has an R3 of 0.21 or higher, as expressed by formula (3). R1 = (886 cm⁻¹) determined by Raman spectroscopy -1 ±5cm -1 (maximum value of the peak at 354cm) ÷ (354cm) -1 ±5cm -1 (the maximum value of the peak at that point)……(1) R2 = produces 952 cm⁻¹ as determined by Raman spectroscopy. -1 ±7cm -1 wavenumber of the peak at the maximum value / cm -1 ……(2) R3=2.95×R1+0.33×R2-315……(3).
4. The catalyst according to any one of claims 1 to 3, wherein, The catalyst is a catalyst in which the active catalytic component is supported on an inert support.
5. The catalyst as described in claim 4, wherein, The inert carrier is silicon dioxide, aluminum oxide, or a combination of silicon dioxide and aluminum oxide.
6. A method for manufacturing the catalyst according to any one of claims 1 to 5, wherein, The manufacturing method includes a preparation step of preparing a compound by adding supply source compounds containing molybdenum, bismuth, and iron to a solvent or solution and integrating and heating the mixture. In the preparation step, the pH of the compound is adjusted to the range of 1.0 to 7.5 by adding a pH adjuster before adding the iron-containing supply source compound.
7. A method for manufacturing unsaturated aldehydes and / or unsaturated carboxylic acids, wherein, The manufacturing method uses the catalyst described in any one of claims 1 to 5.
Citation Information
Patent Citations
Oxide catalyst
JP2017024009A
Catalyst
JP2020142221A
Plastic for sucking up soft contact lenses
JP2021033249A
Method for producing unsaturated aldehyde and / or unsaturated carboxylic acid
WO2015008815A1
Catalyst for manufacturing unsaturated aldehyde and / or unsaturated carboxylic acid and manufacturing method of same, and manufacturing method of unsaturated aldehyde and / or unsaturated carboxylic acid
WO2016136882A1